2012
DOI: 10.1158/0008-5472.can-11-3956
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Sterile 20–like Kinase 1 Suppresses Lymphoma Development by Promoting Faithful Chromosome Segregation

Abstract: The mammalian Hippo signaling pathway has been implicated in oncogenesis in the context of solid tumors such as hepatocellular carcinoma. Mammalian sterile 20-like kinase 1 (MST1), the core component of the Hippo signaling pathway, is highly expressed in hematopoietic cells. However, its possible impact on tumorigenesis in this setting is unknown. In this study, we provide evidence that Mst1 loss in the mouse enhances chemically and genetically induced lymphoma development by inducing chromosomal instability. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Although lymphoma has been described in STK4-deficit mouse, our patient is the first human with this mutation-developed lymphoma. [12] MALT lymphoma is a low-grade B-cell lymphoma of mucosa associated with lymphoid tissue and arises in a number of epithelial tissues, including conjunctiva, salivary gland, thyroid gland, stomach, liver, small bowel, lung and urogenital tract. [13] It constitutes about 5% of all non-Hodgkin lymphomas and almost 50% of all gastric lymphomas in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Although lymphoma has been described in STK4-deficit mouse, our patient is the first human with this mutation-developed lymphoma. [12] MALT lymphoma is a low-grade B-cell lymphoma of mucosa associated with lymphoid tissue and arises in a number of epithelial tissues, including conjunctiva, salivary gland, thyroid gland, stomach, liver, small bowel, lung and urogenital tract. [13] It constitutes about 5% of all non-Hodgkin lymphomas and almost 50% of all gastric lymphomas in adults.…”
Section: Discussionmentioning
confidence: 99%
“…2/2 mice develop spontaneous tumors in liver, colon, and ethyl-N-nitrosoureainduced lymphomas/leukemias (14)(15)(16)(17)(18). Mst1 induces apoptosis through caspase-mediated proteolytic activation and histone H2B phosphorylation (19), or by enhancing Foxo1/3 nuclear entry through phosphorylation of Foxo1 and Foxo3 at S212 and S207, respectively, in fibroblasts and granule neurons (20,21).…”
Section: Mst2mentioning
confidence: 99%
“…Recent studies have also demonstrated the role of Mst1/2 kinases in a YAPindependent mechanism, the so-called noncanonical Hippo pathway. For example, Mst1 suppresses lymphoma development by promoting faithful chromosome segregation, independently of YAP (18). Mst1/2 kinases also execute a variety of functions with multiple partners, such as Foxo1, Foxo3, Akt, and Aurora B, in different biological contexts (19)(20)(21)(22).…”
mentioning
confidence: 99%